2003
DOI: 10.1007/s00221-003-1382-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and GABA modulate dopamine in the pedunculopontine tegmental nucleus

Abstract: The pedunculopontine tegmental nucleus (PPTg) has an important anatomical position connecting basal ganglia and limbic systems with motor execution structures in the pons and spinal cord. It receives glutamatergic and GABAergic input and has additional reciprocal connections with mesencephalic dopaminergic neurons, suggesting that the PPTg plays a key role in frontostriatal information processing. In vivo microdialysis in freely moving rats, in combination with behavioral analysis, was used in this study to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 88 publications
1
20
2
Order By: Relevance
“…For example, Hotsenpiller and Wolf (2003) recently demonstrated that baclofen attenuates conditioned locomotion to cues associated with cocaine administration, and also modulates extracellular glutamate levels in the NAc. Moreover, Steninger and Kretschmer (2003) report that baclofen infused into the pedunculopontine tegmental Fig. 5 Changes in DA efflux in the NAc (line graph) and dAMPH self-administration (bar graph) following baclofen pretreatment in sessions of representative animals.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Hotsenpiller and Wolf (2003) recently demonstrated that baclofen attenuates conditioned locomotion to cues associated with cocaine administration, and also modulates extracellular glutamate levels in the NAc. Moreover, Steninger and Kretschmer (2003) report that baclofen infused into the pedunculopontine tegmental Fig. 5 Changes in DA efflux in the NAc (line graph) and dAMPH self-administration (bar graph) following baclofen pretreatment in sessions of representative animals.…”
Section: Discussionmentioning
confidence: 98%
“…The pedunculopontine nucleus and laterodorsal tegmental nucleus neurons send axons to dopamine-containing areas of the ventral tegmental area and the substantia nigra, as well as to the lateral hypothalamus, thalamus, and basal ganglia, wherein glutamine and acetylcholine may act to modulate reward and learning (Yeomans et al, 1993; Steiniger and Kretschmer, 2003). In addition, the pedunculopontine nucleus may play a role in associative learning and reward as a relay for contextual information to midbrain dopamine neurons (Pan and Hyland, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In rat, dopamine was detected using radiometric assays or microdialysis in the CnF (Versteeg et al, 1976; Saavedra et al, 1979) and PPN (Steiniger and Kretschmer, 2003) that are both part of the MLR in mammals (see Ryczko and Dubuc, 2013). Moreover, dopaminergic fibers were detected in rat brainstem using immunohistochemistry (Kitahama et al, 2000).…”
Section: A New Descending Dopaminergic Pathway Has Been Unraveledmentioning
confidence: 99%